ANALISIS PERILAKU PENGELOLAAN KEUANGAN PADA GENERASI Z DI INDONESIA - Dyah Cahyasari (POLITEKNIK LP3I JAKARTA, 2024)
Based on the 2022 SNLIK survey, the percentage of generation Z's financial behavior is lower than the millennial generation. This is due to the low financial literacy of generation Z. The aims of this study include: (1) obtaining an understanding of the factors that influence the financial behavior of generation Z, and (2) knowing how to improve the financial behavior of generation Z. Z. Systematic Literature Review (SLR) according to the protocol PRISMA was used in this study which refers to international indexed journal publications, from 2018–2022. The majority of research results show a positive effect of financial literacy on financial behavior. Financial literacy is useful for forming generation Z self-efficacy so that they are more confident in determining financial management behavior, but improving financial behavior is not only focused on cognitive aspects but also affective (positive attitude encouragement) and conative (stakeholder support to ensure program success). The importance of the role of parents as the main factor in the socialization of the family environment is to form good and wise financial character, attitudes and behavior.